A Comparison of Local Endolymphatic Sac Decompression, Endolymphatic Mastoid Shunt, and Wide Endolymphatic Sac Decompression in the Treatment of Intractable Meniere's Disease: A Short-Term Follow-Up Investigation - Zheng, Guiliang; Liu, Yupeng; He, Jingchun; Li, Shuna; Zhang, Qing; Duan, Maoli; Yang, Jun; Jin, Yulian (Frontiers in Neurology, 2022)
Background Meniere's disease (MD) is an inner ear disorder, characterized by recurrent attacks of vertigo, low-frequency sensorineural hearing loss, tinnitus, and aural fullness. Endolymphatic sac surgery is an effective treatment to control vertigo attacks but without causing a hearing loss for intractable MD. However, the methods and effects of endolymphatic sac surgery have been controversial for many years, and the relationship between the vertigo control rates of different endolymphatic sac surgery methods is not well-documented. Objectives This study compared the vertigo control rate, hearing outcome, and quality of life (QOL) among different endolymphatic sac surgery, such as local endolymphatic sac decompression (LESD), endolymphatic sac mastoid shunt (ESMS), and wide endolymphatic sac decompression (WESD). Materials and Methods We retrospectively analyzed the patients who underwent endolymphatic sac surgery from January 2008 to June 2019. The control rate of vertigo and QOL scores were compared after 2 years of follow-up. The QOL was scored with validation of the MD patient-oriented symptom-severity index (MDPOSI). The pure tone thresholds of all patients at pre- and postoperation were also compared. Results In total, 83 MD patients with complete follow-up data were included in the study, i.e., 20 patients with LESD, 28 patients with ESMS, and 35 patients with WESD. Results showed a better vertigo control with WESD than the other groups (70% with LESD, 71.4% with ESMS, and 88.6% with WESD). The QOL was improved after surgery in all groups in which the difference was statistically significant (QOL, preoperative vs. postoperative, 38.2 vs. 10.1 with LESD, 37.8 vs. 9.6 with ESMS, and 37.6 vs. 8.3 with WESD), respectively. After endolymphatic sac surgery, the hearing was well-preserved in the three groups [pure tone averages (PTAs), dB, preoperative vs. postoperative, 41.0 ± 19.3 vs. 40.8 ± 17.9 with LESD, 39.7 ± 16.4 vs. 40.8 ± 18.2 with ESMS, and 38.5 ± 18.7 vs. 36.6 ± 19.5 with WESD]. Conclusion Wide endolymphatic sac decompression has a higher vertigo control rate, better improvement of QOL, and relatively higher hearing stability or improvement rate after surgery in patients with MD compared with LESD and ESMS.